A Beijing that you might not know: Geovisualizing selected crimes in Beijing. (October 2019) - Zhou, Jiangping; Yang, Yuling; Zhang, Yanji; Zhang, Chun
China is generally considered a safe place: among the safest for foreigners to visit. For local (long-term) residents and for Chinese criminology scholars, China as a country and its individual cities might be safer compared to many of their foreign peers; however, they might not be as safe as some travel agents claim. To show why this is the case, we crawled and geovisualized the 2015–2016 crime records ( n = 24, 803) available to the public online. The geovisualization shows that the seven crimes ( n = 12, 516) that were most likely to be influenced by space in Beijing were aggravated assault, blackmail, cheating and bluffing, dangerous driving, picking quarrels and provoking trouble, robbery and theft. It also shows a Beijing that many might not have known before.